2016
DOI: 10.1055/s-0035-1564094
|View full text |Cite
|
Sign up to set email alerts
|

β-endorphins Plasma Level is Higher in Lean Polycystic Ovary Syndrome (PCOS) Women

Abstract: Our study showed that the levels of β-endorphins were significantly higher in lean patients with polycystic ovary syndrome than in lean controls. Moreover, β-endorphins levels were found to be correlated with other hormonal parameters. In this respect, β-endorphins may play a role in polycystic ovary syndrome pathophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
(44 reference statements)
0
10
1
1
Order By: Relevance
“…Some evidence indicates that the evolution of PCOS is related to the activity of the endogenous opioid system, in which the main molecule β-endorphin is produced by the pituitary gland and may contribute to PCOS pathogenesis through central effects on gonadotropin secretion and peripheral effects on glucose metabolism. 1 4 In our earlier study, we found higher plasma β-endorphin level in lean PCOS women compared to the healthy controls. 4 Some data have reported that plasma opioid levels correlate with pain perception and pain threshold.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…Some evidence indicates that the evolution of PCOS is related to the activity of the endogenous opioid system, in which the main molecule β-endorphin is produced by the pituitary gland and may contribute to PCOS pathogenesis through central effects on gonadotropin secretion and peripheral effects on glucose metabolism. 1 4 In our earlier study, we found higher plasma β-endorphin level in lean PCOS women compared to the healthy controls. 4 Some data have reported that plasma opioid levels correlate with pain perception and pain threshold.…”
Section: Introductionmentioning
confidence: 74%
“… 1 4 In our earlier study, we found higher plasma β-endorphin level in lean PCOS women compared to the healthy controls. 4 Some data have reported that plasma opioid levels correlate with pain perception and pain threshold. 5 7 …”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…It is a leading cause of infertility and is also associated with an increased risk of metabolic syndrome (MBS), diabetes mellitus type 2, cardiovascular disease, and endometrial cancer. [ 1 ]…”
Section: Introductionmentioning
confidence: 99%